Microscopical aspects od accessory air breathing through a modified stomach in the armoured catfish Liposarcus anisitsi (Siluriformes, Loricariidae) - de Oliveira, C.; Taboga, SR; Smarra, ALS; Bonilla-Rodriguez, G. O. (Faculty Press, 2001)
The presence of an accessory air breathing mechanism as verified by several authors, is widespread among Loricariidae, where modified parts of the digestive tract act primarily as oxygen-exchange organs. An anatomical and histological analysis was carried out on the stomach and intestine of the armoured catfish Liposarcus anisitsi. The data support the assumption that the modified stomach is responsible for holding air and allows blood oxygenation under hypoxia. Experiments demonstrating survival of air breathing Liposarcus in severely hypoxic water support the hypothesis and are discussed.
Keywords: air-breathing organ; catfish; Loricariidae; histology; stomach